Strategi Komunikasi Pemasaran Pariwisata Dispar Aceh Tengah Dalam Promosi Industri Wisata Lokal - Ulfa Khairina (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
This study aims to examine the strategies used and implemented by Central Aceh Tourism Office in promoting the regional tourism industry to local and foreign tourists. This research also look at how by Dinas Pariwisata Aceh Tengah in promotion of local tourism industry to domestic and foreign tourists. The research also looks at how Central Aceh Tourism Office conducts tourism marketing communications by implementing the stages of the communication strategy. This research use descriptive qualitative approach. Data collection techniques using interviews and participatory observation. Determination of informants is done on pruposive sampling technique. Indormants used as primary data sources in this study were representatives from the Central Aceh Tourism Office and the tourist they met in the tourism location. The result showed that Central Aceh Tourism Office was not maximal in carrying out tourism marketing communications.